William B. Randolph papers - Randolph, William B., 1793-; Adams, Richard, active 1793.; Randolph, Elizabeth, active 1793.; Randolph, Peter S.
Personal correspondence and financial, legal, and other papers of Randolph, his father, Peter S. Randolph, his mother, Elizabeth Randolph, his guardian, Richard Adams, and other relatives and friends. The papers reflect the management and economic aspects of Randolph's Virginia plantation, Chatsworth, before the Civil War, especially farming and the buying and selling of slaves. Other topics include the election of Thomas Jefferson to the presidency in 1800, James Monroe's financial affairs (1803-1805), British military activity near Richmond and the burning of Washington, D.C., during the War of 1812, land sales in Kentucky, the formation of the American Colonization Society, the 1829 presidential inauguration of Andrew Jackson, the Tredegar Iron Works, Richmond, Va., fear of a slave uprising near Richmond (1830-1831), the operation of a wheat reaper (1842), and Civil War military activity in western Virginia. Legal papers relate to a contested election for the Virginia House of Delegates in 1835 and a contract (1839) between Randolph and P. S. Jones wherein Randolph was named sheriff of Henrico County, Va., while Jones performed all the duties and received all emoluments of the office.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Plantation owner from Virginia. Died 1874.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Jackson, Andrew, -- 1767-1845 -- Inauguration, 1829.; Jefferson, Thomas, -- 1743-1826.; Jones, P. S., -- active 1849.; Monroe, James, -- 1758-1831.; Randolph family; American Colonization Society; Tredegar Iron Works (Richmond, Va.); Virginia. -- General Assembly. -- House of Delegates; Agriculture -- Virginia; Land speculation -- Kentucky; Plantation life -- Virginia; Plantations -- Virginia; Presidents -- United States -- Election -- 1800.; Sheriffs -- Virginia -- Henrico County; Slave insurrections -- Virginia -- Richmond; Slave trade -- Virginia; Wheat -- Harvesting machinery; Chatsworth Plantation (Va.); Richmond (Va.) -- History -- War of 1812.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- War of 1812 -- Campaigns; United States -- History -- War of 1812 -- Participation, British; Virginia -- History -- Civil War, 1861-1865 -- Campaigns; Virginia -- History -- War of 1812.; Washington (D.C.) -- History -- War of 1812.; Plantation owners